Analysis of Factors Affecting Continuance Usage Intention of Linkaja Applications - Nurul Reskyana; Candiwan Candiwan (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2020)
In 2019 PT Fintek Karya Nusantara launched the LinkAja Application which migrated from the T-Cash. As a product of BUMN that has network support throughout Indonesia, LinkAja should be able to become the number one e-wallet player because it has a great opportunity to reach a bigger market share compared to other e-wallet applicators. However, based on LinkAja Application, user data has not reached the target and there is a gap between the realization of the user and the active user of the Application. This study aims to analyze the factors that influence the continuance intention to use LinkAja in terms of gender using the Theory of DOI and Trust Building Framework. Researchers used the SEM and PLS methods in analyzing data. The results of the study stated that reputation is the most influence on trust, followed by variable mobility, security, and customization. The trust variable positively influences the continuance intention, while a higher perceived risk variable will reduce the intention to continue using the LinkAja application. Also, the effect of Mobility and Reputation on Trust is higher for male than female customers, while the effect of Customization and Security on Trust is higher for women than for men.